CURRENT TRENDS AND CHALLENGES IN THE INTEGRATION OF TECHNOLOGY IN ENGLISH LANGUAGE TEACHING: A CASE STUDY AT MAN 2 KOTA MAKASSAR - Salsyabila, Andi Namirah Rezky; Munir, Munir; Aeni, Nur (State University of Makassar, 2025)
This study explores the current trends and challenges in integrating technology into English Language Teaching (ELT) at MAN 2 Kota Makassar. Using a qualitative descriptive method, the research involved classroom observations and interviews with three English teachers. Findings show that teachers use tools such as PowerPoint, Canva, ChatGPT, and WhatsApp to enhance learning, yet face various challenges including inadequate infrastructure, limited access for students, and lack of digital literacy. This paper provides an in-depth discussion on how these trends align with global developments and analyzes the barriers that may hinder effective integration. The study highlights the importance of institutional support and continuous professional development for teachers to overcome existing challenges.Keywords: Technology Integration; ELT; Digital Tools; Teaching Challenges; ICT in Education